2018
DOI: 10.1111/cts.12579
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dermal Absorption of Aluminum from a Representative Antiperspirant Formulation Using a 26Al Microtracer Approach

Abstract: A clinical pharmacokinetic study was performed in 12 healthy women to evaluate systemic exposure to aluminum following topical application of a representative antiperspirant formulation under real‐life use conditions. A simple roll‐on formulation containing an extremely rare isotope of aluminum (26Al) chlorohydrate (ACH) was prepared to commercial specifications. A 26Al radio‐microtracer was used to distinguish dosed aluminum from natural background, using accelerated mass spectroscopy. The 26Al citrate was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Following topical application, 0.01% of Al was assumed to be absorbed based on reports of dermal Al absorption from Al chlorohydrate in humans (Flarend et al 2001;de Ligt et al 2018).…”
Section: Bioavailability Expressed As Approximate Systemic Al Exposurementioning
confidence: 99%
“…Following topical application, 0.01% of Al was assumed to be absorbed based on reports of dermal Al absorption from Al chlorohydrate in humans (Flarend et al 2001;de Ligt et al 2018).…”
Section: Bioavailability Expressed As Approximate Systemic Al Exposurementioning
confidence: 99%
“…Based on their measurements and information on the mean renal excretion rate of 85% of the absorbed aluminium (Priest et al 1995), the authors calculated an average absorption rate of 0.014% (Flarend et al 2001). Recently published preliminary data from another, more comprehensive human toxicokinetics study (de Ligt et al 2018) show very similar absorption rates through intact skin. An in vitro study (Pineau et al 2012) showed average penetration rates through intact skin of 1.6%, 0.6% and 2.0% for the formulations "deodorant spray", "roll-on" and "stick", respectively (calculated according to the "Notes of Guidance for the Testing of Cosmetic Ingredients and their Safety Evaluation" of the Scientific Committee on Consumer Safety of the European Commission (SCCS 2018) as the sum of the aluminium contents in living epidermis, dermis and receptor fluid).…”
Section: Absorption Distribution Metabolism Excretion (Adme)mentioning
confidence: 99%
“…The results confirmed that antiperspirants play a minor role in the total systemic exposure to the aluminium salts. Moreover, shaving or daily use did not influence the absorbed quantities of 26 Al (de Ligt et al, 2018).…”
Section: Composition Of Thermal Spring Watersmentioning
confidence: 79%